Portuguese Azulejos, World Heritage - Matos, M. (2015)
Few forms of artistic expression capture the nature and the way of life of the Portuguese as the azulejo does. Manufactured and used in other countries, sometimes with superior technical quality, some aspects, however, impart to the way it was and still is used in Portugal an unparalleled originality since the first batches, imported from Andalusia in the late fifteenth century, to the present day when it is used to line the public spaces of modern towns. This continued use is, in itself, a distinguishing aspect when compared to other European cases; however it is its capacity of renewal according to the needs of a given epoch that mostly marks the difference. The changes in taste, fashions, aesthetic expressions, or new requirements have found in the azulejo a flexible support, adaptable to new duties, adjustable to evolving social needs, but also shaping up to its different clienteles. With designs of lesser or greater erudition, both religious and profane, narrating mythological or historic facts with equal propensity, portraying everyday life or simply adjusting to the expressions of other arts, such as textiles, wood carving or metalwork, the Portuguese azulejo always “found” ways to adjust to new times and new ways and this aspect, allied to its natural duration as a finishing was a winning trump card. For all these reasons, the Portuguese General Directorate for Cultural Heritage intends to proceed with the candidacy to UNESCO in 2018 for the classification of architecturally integrated Portuguese azulejos as World Heritage. The preparations for this application began in 2009 with the partnership that the Museu Nacional do Azulejo (MNAz) established with the Laboratório Nacional de Engenharia Civil (LNEC). Following that partnership, teams were formed involving researchers from both organizations, and research projects have been carried out: on specific aspects related to the manufacture of azulejos; to determine causes and mechanisms so far unknown of their decay; and to verify analytically assumptions related to their history. The corpus of results will allow a better understanding of the azulejo and, hopefully, a much more effective approach to the conservation of architecturally integrated panels, ensuring that this most Portuguese of material cultural heritages will endure to be transmitted to future generations.